Perceptions of the English Language Intensive Course for Overseas Students’ Program Toward Vocabulary Learning Strategies - Artika, Febria Sri; Fitriani, Suci (Jurnal Educative: Journal of Educational Studies, 2024)
The objective of this research is to investigate the benefits received by international students at the English Language Intensive Course for Overseas Students' program (ELICOS) of the University of Canberra College English Language Centre (UCCELC) in Australia in implementing Vocabulary Learning Strategies (VLS). The benefits are in terms of finding new vocabulary outside of the classroom, writing the words directly while encountering new words, making a connection for the meaning of the words, studying the aspects of the new words, rehearsing, saying the new words aloud and jotting the word down, getting an image of the first time they met the words, and using new vocabulary in daily conversation. A qualitative design was used to collect information from six international students from various nations, including Indonesia, China, the Philippines, and Japan, utilising interviews. The interview data were analysed and presented using qualitative research processes such as coding, grouping, argument creation, and drafting. The findings of this study demonstrated that students in the ELICOS program use a variety of vocabulary learning strategies, including cognitive, metacognitive, memory, and social strategies. Furthermore, all students reported that they gained a considerable beneficial impact on their language learning proficiency by applying behaviors of some particular vocabulary learning strategies These findings have significant implications for increasing the quality of language teaching and learning processes, as well as enriching the research repertory in the field of VLS. Bahasa Inggris untuk Mahasiswa Luar Negeri (ELICOS) dari University of Canberra College English Language Centre (UCCELC) di Australia dalam mengimplementasikan Strategi Pembelajaran Kosakata (Vocabulary Learning Strategies - VLS). Manfaatnya adalah menemukan kosakata baru di luar kelas, menulis kata-kata tersebut secara langsung ketika bertemu dengan kata-kata baru, membuat hubungan makna kata-kata tersebut, mempelajari aspek-aspek dari kata-kata baru tersebut, berlatih, mengucapkan kata-kata baru tersebut dengan lantang dan menuliskan kata tersebut, mendapatkan gambaran ketika pertama kali bertemu dengan kata-kata tersebut, dan menggunakan kosakata baru tersebut dalam percakapan sehari-hari. Untuk mengumpulkan informasi dari enam mahasiswa internasional dari berbagai negara, termasuk Indonesia, Cina, Filipina, dan Jepang, dengan menggunakan wawancara. Data wawancara dianalisis dan disajikan dengan menggunakan proses penelitian kualitatif seperti pengkodean, pengelompokan, pembuatan argumen, dan penyusunan. Temuan dari penelitian ini menunjukkan bahwa siswa dalam program ELICOS menggunakan berbagai strategi pembelajaran kosakata, termasuk strategi kognitif, metakognitif, memori, dan sosial. Selain itu, semua siswa mengakui bahwa mereka mendapatkan dampak yang cukup menguntungkan pada kemampuan belajar bahasa mereka dengan menerapkan aspek-aspek VLS. Temuan ini memiliki implikasi yang signifikan untuk meningkatkan kualitas proses belajar mengajar bahasa, serta memperkaya khazanah penelitian di bidang VLS.